Women in Latin American science: gender parity in the twenty-first century and prospects for a post-war Colombia. Issue 1 (1st January 2019) - López-Aguirre, Camilo
ABSTRACT: The aim of this study was to evaluate the status of gender parity in science in Colombia throughout the twenty-first century. Data were decomposed by research area, researcher rank level and academic level. Gender disparity was also estimated for changes in average age, access to scholarships for postgraduate studies, and number of doctoral graduates. Using logistic function modeling, temporal projections into the future were performed in order to estimate how long could it take to reach gender parity. Medical and health science is the only field to have reached gender parity, while also showing a steady decrease in women's representation across time. On the other hand, engineering, humanities and natural sciences had the lowest percentages of women's representation. Women researchers showed a decreasing presence as they move upward to more senior levels, exemplifying the "leaky-pipeline phenomenon" common in science. Possible drivers of these results are analyzed, suggesting that a combination of lack of research funding, insufficient legal framework, pre-existing biases, and poor protection of women's rights inhibits women's participation in science. It is estimated that, without any action to change current trends, it could take between 10 (humanities) and 150 (engineering) years to reach gender parity across all research areas.